Bermain Terapeutik terhadap Tingkat Kecemasan Anak yang Mendapat Terapi Inhalasi - Olivia Bawaeda; Dessie Wanda (Journal of Telenursing (JOTING), 2022)
This study aims to identify the effectiveness of therapeutic play on the anxiety level of children receiving inhalation therapy. The method used is a systematic review using the PICO strategy on the Scopus, Science Direct, Clinical Key, and Proquest databases. The results showed that therapeutic play effectively reduced and eliminated anxiety in children during inhalation therapy procedures. In conclusion, therapeutic play is a non-pharmacological therapy that nurses can do to children who experience anxiety due to inhalation therapy procedures. Keywords: Children, Therapeutic Play, Anxiety, Inhalation Therapy